Propriedades estruturais, eletrônicas e ópticas dos cristais anidros das bases pirimidínicas: simulações na teoria do funcional da densidade - Silva, Mauricélio Bezerra da (2016)
Uracil (U), thymine (T) and cytosine (C) are nitrogenous bases of the pyrimidine type. These along with the other two bases purines adenine (A) and guanine (G), form the essential basis of the ribonucleic acid molecule (RNA) and acid deoxyribonucleic (DNA), which contains the genetic information used by living cells. DNA and RNA crystals have enough attractive semiconductor characteristics in the field of organic electronics, and for this reason are strong candidates in the manufacture of molecular nanodevices. However, advancements in this area are still premature. This work presents the structural, electronic and optical of the anhydrous crystals of pyrimidine nucleotide bases. The theoretical results were obtained after calculations based on density functional theory (DFT), with an energy cut of 830 eV, using the approximations of local density (LDA) and generalized gradient (GGA), this last one including empirical corrections to dispersive interactions (PBE + TS) available at CASTEP package. The computational results were then compared with the crystals experiments of optical absorption and UV absorption. Theoretical studies applied to the crystals cytosine, thymine, adenine and guanine are already available in the literature. However, it is still missing a description using a more sophisticated functional as was used in this work. The absorption values obtained for the uracil, thymine and cytosine crystals shows that these have, respectively, indirect, direct and indirect gaps with values of 4.03 eV, 3.80 eV and 4.20 eV. As expected, the theoretical results exhibited energy gaps lower than the experimental values: 3.45 eV (U), 3.47 eV (C) and 3.50 eV (T). Effective mass calculations confirm literature data that the bases are generally wide gap semiconductor. Finally, the results obtained by DFT suggest a reasonable degree of optical anisotropy for the absorption and complex dielectric function, especially in uracil and thymine. As expected, the theoretical results exhibited energy gaps lower than the experimental values: 3.45 eV (U), 3.47 eV (C) and 3.50 eV. (T). Effective mass calculations confirm the literature data that the bases are semiconductor with wide gaps. Finally, the results obtained by DFT suggest a reasonable degree of optical anisotropy for the absorption and complex dielectric function, especially in the uracil and thymine cases.